"Why Archaeology is important for Theology" - Johnson, Cayetana Heidi (Studia Nauk Teologicznych PAN, 2021)
The Old Testament is clearly a mixture of myths and real historical figures and events. There is no question about the contribution of mythology since much of Genesis has been formed from common mythological accounts from all over the ancient Near East. The stories of Creation, the primordial couple, the Garden of Eden, Cain and Abel, the Great Flood, and much more, are commonplace narratives throughout the region. Although these accounts are mythological, it does not mean that they have not been shaped by real events. Specialists speculate about a great flood that took place in the Near East as a result of rising water levels at the end of the last Ice Age (around 5000 BC). This coincided at a time when the Agricultural Revolution had taken over Egypt and the Fertile Crescent. Various peoples of the Levant adopted mythological narratives and reformulated them to create their own unique and original tales. Some of the main figures of the Bible, such as Adam and Eve, Noah, Lot, as well as the patriarchs (Abraham, Isaac, and Jacob) were a result of their own composition, but as can be seen with the patriarch Abraham, who was not an exclusive figure of the Hebrew people, his conversion to monotheism is, however, something peculiar to the spiritual creativity of the Jewish people. Here as in the composition of the New Testament, archeology is the necessary aid to locate the reality and the truth of sacred history and its development in human time.